2020
DOI: 10.1038/s41612-020-0124-2
|View full text |Cite
|
Sign up to set email alerts
|

Half the world’s population are exposed to increasing air pollution

Abstract: Air pollution is high on the global agenda and is widely recognised as a threat to both public health and economic progress. The World Health Organization (WHO) estimates that 4.2 million deaths annually can be attributed to outdoor air pollution. Recently, there have been major advances in methods that allow the quantification of air pollution-related indicators to track progress towards the Sustainable Development Goals and that expand the evidence base of the impacts of air pollution on health. Despite effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
157
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(159 citation statements)
references
References 23 publications
0
157
0
2
Order By: Relevance
“…More than 90% of the global population live in areas exceeding the World Health Organization global air quality guidelines (WHO AQGs) for particulate matter with diameter of less than 2.5 micrometres (PM 2.5 ), i.e. 10 μg/m 3 annual average (Shaddick et al 2020 ). In 2004, WHO and the World Bank initiated the first comprehensive evaluation of ambient air pollution in the global burden of disease (GBD) study (Ezzati et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of the global population live in areas exceeding the World Health Organization global air quality guidelines (WHO AQGs) for particulate matter with diameter of less than 2.5 micrometres (PM 2.5 ), i.e. 10 μg/m 3 annual average (Shaddick et al 2020 ). In 2004, WHO and the World Bank initiated the first comprehensive evaluation of ambient air pollution in the global burden of disease (GBD) study (Ezzati et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…As indicated in the fifth assessment report by the Intergovernmental Panel on Climate Change (IPCC), climate change manifests in a global increase of air and sea temperature and results in the loss of polar snow and ice, sea level rise, as well as the increased occurrence of extreme weather events [1]. This is accompanied by a directly anthropogenically induced environmental change expressed, for example, by extensive deforestation [2,3], the land take of cities and settlements [4,5], and the increasing pollution of the environment [6][7][8]. The ramifications of these changes affect the livelihoods of humanity directly: Decreasing snow cover in the mountains threatens the tourism-based economies of regions and entire countries [9,10].…”
Section: The Need For Forecastsmentioning
confidence: 99%
“…Again, one reviewed study may employ more than one sensor, and since some sensors can produce multiple data types (e.g., MODIS optical and thermal), the total counts between sensors and sensor types differ slightly. Optical EO data was used 160 times, followed by SAR (17), thermal (10), passive microwave (9), and altimetry data (8). Gravimetry and scatterometer data have been used in one case each.…”
Section: Technical Aspectsmentioning
confidence: 99%
“…Air quality monitoring in many countries has shown that the levels of common pollutants have increased from 1980 until now. During 2010–2016, an estimated 55.3% of the global population were exposed to dangerous levels of air pollution ( Shaddick et al, 2020 ). Therefore, a major global health risk to the world’s population is air pollution, with more than 90% of people living in areas that do not meet the 2017 World Health Organization’s (WHO) recommended threshold of air quality levels ( Health Effects Institute, 2019 ).…”
Section: Introductionmentioning
confidence: 99%